The Biology and Function of Extracellular Vesicles in Cancer Development - Zhang, Xinyi; Liu, Dianfeng; Gao, Yongjian; Lin, Chao; An, Qingwu; Feng, Ye; Liu, Yangyang; Liu, Da; Luo, Haoming; Wang, Dongxu (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) can effectively change their biological effects through proteins, metabolites, and nucleic acids delivered to recipient cells. EVs have anti-tumor roles which are based on their biology and function in cancer development. This anti-tumor effect is achieved through EVs to delivered proteins, metabolites, and nucleic acids by cell communication. The character of cell-to-cell communication can be potentially applied to the therapy of certain cancers, such as gastric cancer. In addition, EVs can be used as an effective vesicle to deliver their cargo, including ncRNAs, peptides, and drugs, to targeted tumor tissues. In addition, EVs have the ability to regulate cell apoptosis, autophagy, proliferation, and migration in cancer. The ncRNA and peptides that were engaged with EVs were associated with cell signal pathways in cancer development. This review focuses on the composition, cargo, function, mechanism, and application of EVs in cancer.